Microstructure and mechanical properties of AZ91 magnesium alloy fabricated by multi-layer and multi-pass CMT based WAAM technique - Chengxuan Yin; Junqi Shen; Shengsun Hu; Zhongrui Zhang (Results in Engineering, 2023)
The block sample of AZ91 magnesium alloy was fabricated via multi-layer and multi-pass wire and arc additive manufacturing (WAAM) based on cold metal transfer (CMT) technique, and the dimension of the sample could better meet the requirement of actual production compared with the thin-walled sample prepared by the multi-layer and single-pass process. The sample was composed of equiaxed grains. The grain size was homogeneous in the deposited passes, while there was an obvious difference of grain size in the junction area of the deposited passes. The average tensile strength and elongation of the sample in the traveling direction were 246.7 MPa and 19.4%, respectively, while those in the pass overlap direction perpendicular to the traveling direction were 127.1 MPa and 11.6%, respectively, due to the formation of defects and brittle second phases.